Natural polyphenols inhibit the dimerization of the sars-cov-2 main protease: The case of fortunellin and its structural analogs - Panagiotopoulos, Athanasios; Karakasiliotis, Ioannis; Kotzampasi, Danai Maria; Dimitriou, Marios; Sourvinos, George; Kampa, Marilena; Pirintsos, Stergios; Castanas, Elias; Daskalakis, Vangelis (My University, 2021)
3CL-Pro is the SARS-CoV-2 main protease (MPro). It acts as a homodimer to cleave the large polyprotein 1ab transcript into proteins that are necessary for viral growth and replication. 3CL-Pro has been one of the most studied SARS-CoV-2 proteins and a main target of therapeutics. A number of drug candidates have been reported, including natural products. Here, we employ elaborate computational methods to explore the dimerization of the 3CL-Pro protein, and we for-mulate a computational context to identify potential inhibitors of this process. We report that for-tunellin (acacetin 7-O-neohesperidoside), a natural flavonoid O-glycoside, and its structural analogs are potent inhibitors of 3CL-Pro dimerization, inhibiting viral plaque formation in vitro. We thus propose a novel basis for the search of pharmaceuticals as well as dietary supplements in the fight against SARS-CoV-2 and COVID-19.
Keywords: COVID-19; SARS-CoV-2; Molecular simulations; Metadynamic; Natural products